2002
DOI: 10.1080/13623690208409634
|View full text |Cite
|
Sign up to set email alerts
|

Obstetrics during civil war: Six months on a maternity ward in Mallavi, Northern Sri Lanka

Abstract: A long-term, large-scale ethnic armed conflict continues in Sri Lanka, where militant separatists control a northern section of the island. The conflict has resulted in a large population of internally displaced persons and a shortage of medical staff. Drug and equipment shortages compound the difficulty in access to medical care. This article reports the experiences from 1 November 2000 to 30 April 2001 recorded by review of medical records and by interviews, in the peripheral unit, in a separatist controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…However, almost all mothers had received some ANC at a level comparable to the national situation (Ministry of Health, 2007). These results were supported by the findings of two studies in similar areas-Mallavi (94%) and Kopay (98.2%)within the Northern Province (Simetka et al, 2002;Surenthirakumaran, 2007). Increased attendance to antenatal clinics despite the conflict situation is a favorable indication for ANC utilization; thus, service providers should focus more on quality of care rather than increasing the frequency of visits routinely.…”
Section: Discussionsupporting
confidence: 81%
“…However, almost all mothers had received some ANC at a level comparable to the national situation (Ministry of Health, 2007). These results were supported by the findings of two studies in similar areas-Mallavi (94%) and Kopay (98.2%)within the Northern Province (Simetka et al, 2002;Surenthirakumaran, 2007). Increased attendance to antenatal clinics despite the conflict situation is a favorable indication for ANC utilization; thus, service providers should focus more on quality of care rather than increasing the frequency of visits routinely.…”
Section: Discussionsupporting
confidence: 81%
“…Sri Lankan migrants in Norway are mainly Tamils from the conflict affected regions of Sri Lanka [15]. Rates of stillbirths, neonatal and maternal deaths have been reported to be higher in these regions than in other regions of Sri Lanka [16-18]. We used the PMR for Sri Lanka as a whole in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas trauma patients make up a comparably minor portion of critically ill patients except in military hospitals, there is an abrupt increase in acute cardiac, cerebrovascular, and medical diseases (68). Simetka et al (69) reported on a significant increase in the rates of low birth weight, stillbirths, neonatal deaths, and maternal mortality during civil war in Sri Lanka. Particularly in times of war, occupancy of ICU beds is often paradoxically lower than during peace, since ongoing conflicts, lack of transportation possibilities, high numbers of severely injured civilians, and extreme poverty with lack of financial resources prevent patients from presenting to hospitals or other health care facilities (70,71).…”
Section: Supporting Disciplinesmentioning
confidence: 98%